Determinants of Stunting in Toddlers in the Tetaf Health Center Working Area, Kuatnana District, South Central Timor Regency (TTs) - Betti, Dentriani Elisma; Adu, Apris A; Manurung, Imelda FE (Journal of Public Health for Tropical and Coastal Region, 2024)
AbstractIntroduction: Stunting is a condition in which a person's height is less than normal at a similar age and sex. The presence of stunting indicates prolonged (chronic) malnutrition. The cause of stunting is low nutrient intake in the first of 1,000 days of life, which is from the fetus until two years old. This study aimed to analyze the determinants of stunting in toddlers in the working area of Tetaf Health Center, Kuatnana District, South Central Timor Regency (TTS).Methods: This study was an analytical survey with a case-control design. The number of samples was 134 people who were divided into 67 case groups and 67 control groups. Data analysis technique using chi-square statistical test.Results: The results showed that there was a significant association of maternal knowledge (p-value = 0.000, OR = 7.744), maternal parenting (p-value = 0.000, OR = 6.384), history of anemia in pregnant women in the third trimester (p-value = 0.000, OR = 7.744), birth weight (p-value = 0.000, OR = 5.608), basic immunization status (p-value = 0.000, OR = 7.939), nutritional status of toddlers (p-value = 0.000, OR = 3.913), and Residential Environmental Sanitation (p value = 0.000, OR = 5.443) with stunting incidence among toddlers in the Tetaf Health Center Working Area, Kuatnana District, South Central Timor District.Conclusion: Based on the results of the study, it is recommended for prospective parents/families of toddlers to prepare themselves before marriage and during pregnancy, bring pregnant women who are about to give birth to health centers or health facilities, expand their knowledge to be able to prepare sufficient nutrition so that they can reduce the risk of stunting in toddlers.